دور التدقيق المشترك في رفع كفاءة استخدام المعاينة الاحصائية في تدقيق الحسابات (دراسة ميدانية في بيئة الأعمال السورية) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The study aimed at identifying the method of joint auditing of the financial statements and the stages that must be carried out to complete the audit process using the statistical survey. To achieve this objective, a field study was carried out through the creation of a questionnaire distributed to a sample of practicing auditors according to the Association of Chartered Accountants in Damascus, and then analyzing the results and testing the hypotheses using SPSS. And research found the following results: There is the role of the joint audit in raising the efficiency of the use of a preview qualities in the audit and special evaluation of test results jointly. There is a role for joint auditing in raising the efficiency of the use of the examination of variables in the audit, especially the assessment of relative importance in a joint manner. There is a role for joint auditing in raising the efficiency of determining the size of the sample and the factors affecting it, especially the acceptable risk rate in common. There is the role of the joint audit in reducing the risk of use of statistical sampling in audit, special audit is divided between the auditors' joint accounts on the basis of the applicable auditing or corporate functions business cycles. هدفت الدراسة إلى التعرف على أسلوب التدقيق المشترك للبيانات المالية  والمراحل  التي يجب القيام بها لإنجاز عملية التدقيق باستخدام المعاينة الاحصائية . ولتحقيق هذا الهدف تم القيام بدراسة ميدانية من خلال إنشاء استبانة تم توزيعها على عينة من مراجعي الحسابات الممارسيين حسب جمعية المحاسبين القانونين في دمشق ومن ثم تحليل النتائج واختبار فرضيات البحث باستخدام البرنامج الإحصائي SPSS . و توصل البحث إلى النتائج الأتية: يوجد دور للتدقيق  المشترك في رفع كفاءة استخدام معاينة الصفات في تدقيق الحسابات و خاصة تقييم نتائج الاختبار بشكل مشترك. يوجد دور للتدقيق  المشترك في رفع  كفاءة استخدام معاينة المتغيرات في تدقيق الحسابات وخاصة تقدير الأهمية النسبية بشكل مشترك. يوجد دور للتدقيق  المشترك في رفع كفاءة تحديد حجم العينة والعوامل المؤثرة بها وخاصة معدل الخطر المقبول بشكل مشترك. يوجد دور للتدقيق المشترك في تخفيض مخاطر استخدام المعاينة الاحصائية في تدقيق الحسابات و خاصة يتم تقسيم أعمال المراجعة بين مدققي الحسابات المشتركة على أساس دورات التدقيق المعمول بها أو وظائف الشركات.